PENGGUNAAN MEDIA SOSIAL SEBAGAI SUMBER PEMBELAJARAN YANG EFEKTIF DI KALANGAN PELAJAR - Lesty Annatul Annisa; Diya Alya; Samsul Bahri (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
In today's digital era, social media is not only used as a communication and entertainment tool but also as an effective source of learning for students. This article discusses the utilization of social media as a learning medium, focusing on platforms commonly used by students such as YouTube, Instagram, Twitter, and Facebook. With its ability to provide quick access to information, flexibility in learning time, and potential for collaboration, social media can support the educational process beyond the classroom. However, using social media for learning also faces challenges such as the risk of distraction, issues with information validity, and the need for adequate digital literacy. This article aims to explore the benefits, challenges, and strategies to optimize the use of social media in education, as well as provide recommendations for students and educators to effectively leverage social media to support teaching and learning processes.